Alternative vascular access for haemodialysis: a single centre experience in transhepatic and intracardiac catheters - Barros,Francisca (2014)
Introduction: Vascular access for haemodialysis represents a major problem for patients undergoing this technique. The construction of fistulas or grafts is not always feasible, and a central venous catheter remains as the sole option. Exhaustion of the common sites for central venous catheters placement is common, which sometimes leads to new life-saving approaches. Methods: We retrospectively reviewed the charts of four patients who underwent intracardiac or transhepatic dialysis catheter placement in our clinic between January 2003 and November 2010. Two patients received an intracardiac catheter, one patient received a percutaneous transhepatic catheter and one patient had initially a transhepatic catheter followed by an intracardiac catheter when dysfunction of the former developed. Overall, five intracardiac and four transhepatic catheters were placed. Results: In our patients, when the first procedure was placement of intracardiac catheter the access average survival was 36 months (24-48 months), compared to the use of transhepatic catheters as first approach, with an access survival of 1.75 months (0.5-3 months) for the latter. The two patients who underwent intracardiac catheter replacement died in the post-operative period. Two transhepatic catheters needed replacement, and average catheter survival was 13 months (2 -24 months). Discussion: Our results provide evidence that these techniques can be considered as a last option for patients with exhaustion of vascular access and unsuitable for peritoneal dialysis or kidney transplantation.